THE EXPERIENCE OF GENERAL DOSIMETRY PASPORTIZATION OF THE TERRITORIES AFFECTED BY THE INTENSIVE CHERNOBYL FALLOUT IN UKRAINE - L. N. Kovgan; L. A. Likhtarov; O. N. Perevoznikov (Радиационная гигиена)
Ukraine legislation for the decision making after the Chernobyl accident is characterized. The brief description of two main methodological documents which regulate the requirements to the monitoring and calculation of annual passport and retrospective-prospective doses is given. The generalized results of the dosimetric passportization and retrospective-prospective doses reconstruction for 2161 settlements under annual passportization as well as the example of "settlement's dosimetric passport" are given.